Exploring SEIPS 2.0 as a model for analyzing care transitions across work systems. (October 2020) - Werner, Nicole E.; Rutkowski, Rachel; Graske, Amy; Finta, Mary K.; Sellers, Craig R.; Seshadri, Sandhya; Shah, Manish N.
Abstract: Care transitions across healthcare settings, specifically between the emergency department (ED) and the home, are pervasive among older adults, and represent persistent healthcare quality and safety challenges. Care transitions cross multiple distinct work systems, representing a conceptual and methodological challenge for the field of Human Factors/Ergonomics - how to analyze a process that occurs across multiple work systems. As an initial step in determining how to study care transitions across work systems, we applied the Systems Engineering Initiative for Patient Safety (SEIPS) 2.0 model, specifically the concept of configuration, to explore older adults' ED-to-home transitions. Our results suggest that configuration is useful for identifying and modeling work system barriers that interact across systems, but does not explicitly allow for the identification and analysis of the system boundaries that are crossed. To fully capture the complexity associated with care transitions, future iterations of SEIPS should introduce a mechanism to capture specific boundary types, so that system analysis can capture when and which boundaries are crossed. Highlights: Older adults' care transitions should be conceptualized as a holistic patient journey. Patient journeys cross multiple boundaries with interacting barriers and facilitators. Configuration has potential for work systems analysis of multi-system journeys.